REBT Counseling Reduces Anxiety in Bullied Teenagers at MTSN X Bekasi - Suryani, Neni; Nurhayati, Nurhayati; Permatasari, Tria Astika Endah (GLOBAL HEALTH SCIENCE GROUP, 2024)
Bullying remains a prevalent issue among adolescents in schools, often without adequate counseling or intervention programs in place to mitigate the physical and psychological impacts. This study aims to assess the efficacy of Rational Emotive Behavior Therapy (REBT) counseling in reducing anxiety among bullied adolescents. Conducted as a quasi-experimental pre-post test with a control group design, the study targeted students in grades VII and VIII at MTSN X Bekasi. Fifty students were selected for both the intervention and control groups. The intervention group received group counseling utilizing the REBT method, while the control group received no treatment. Data analysis involved Dependent Samples Test and Independent Samples Test. Results indicated a significant decrease in anxiety levels among adolescents who underwent REBT intervention, with a reduction of -10.46 (p-value <0.05). The effectiveness of REBT counseling was evident in the significant decrease in anxiety levels (p-value <0.001), contrasting with the control group, where anxiety levels remained relatively unchanged (p-value 0.209). These findings underscore the effectiveness of REBT counseling in alleviating anxiety among bullied adolescents. It emphasizes the importance of implementing REBT-based counseling interventions in schools through collaborative efforts among stakeholders.